PROBLEMS AND DIRECTIONS OF DEVELOPMENT OF CORRELATION-EXTREMAL NAVIGATION SYSTEMS OF AIRCRAFTS - Oleksandr M. Sotnikov; Volodymyr A. Tarshyn; Pavlo V. Openko (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
On the basis of analysis of scientific achievements in the field of correlation-extremal systems of piloted aircraft and the peculiarities of their application are discussed exist-ing problems and ways to enable high-precision guidance of aircraft.